Ultrasonic monitoring to assess the impacts of forest conversion on Solomon Island bats. Issue 2 (28th June 2016) - Davies, Tammy E.; Ruzicka, Filip; Lavery, Tyrone; Walters, Charlotte L.; Pettorelli, Nathalie
Abstract : Forest conversion is a major threat to biodiversity and is particularly acute on tropical islands, which are home to a high number of endemic species and important sites for conservation. Our work provides interesting information on both the impact of forest conversion on bat assemblages, and the application of acoustic monitoring of bats for a data‐deficient area of the Solomon Islands. We found significant differences in the mean forearm length across habitats, and use our experience to discuss the challenges of acoustic monitoring in a remote and poorly studied region. Abstract: Paleotropical islands are experiencing extensive land‐use change, yet little is known about how such changes are impacting wildlife in these biodiversity hotspots. To address this knowledge gap, we characterized bat responses to forest conversion in a biodiverse, human‐threatened coastal rainforest habitat on Makira, Solomon Islands. We analysed 200 h of acoustic recordings from echolocating bats in the four dominant types of land use on Makira: intact forest, secondary forest, food gardens and cacao plantations. Bat calls were identified to the species level using a supervised classification model (where labelled data are used to train the system). We examined relative activity levels and morphological traits across habitats. Relative activity levels were highest in intermediately disturbed habitats and lowest in the most heavily disturbed habitat, although these differences were not significant. There were significant differences in the mean forearm length of bat assemblages across habitats, with the highest mean forearm length found in the most open habitat (Cacao). Overall, our study constitutes the first detailed exploration of anthropogenic effects on mammalian diversity in the Solomon Islands and includes the first acoustic and morphological information for many bat species in Melanesia. We use our experience to discuss the challenges of acoustic monitoring in such a remote and poorly studied region.